An update to the taxonomy of Sericini (Coleoptera: Scarabaeidae: Sericinae) from Xizang, China - Yang, Zhi-Yu; Liu, Wan-Gang; Bai, Ming; Ahrens, Dirk; Zheng, Ying-Juan; Liu, Yang (Zootaxa, 2026)
In this paper we update the knowledge on the species of Sericini occurring in Xizang, China. Seven new species are described: Gynaecoserica medogensis Liu W., Ahrens & Yang, sp. nov., Maladera baibungensis Liu W., Ahrens & Yang, sp. nov., Neoserica jiagaensis Liu W., Ahrens & Yang, sp. nov., N. nyingchiana Liu W., Ahrens & Yang, sp. nov., N. parazhehaoi Liu W., Ahrens & Yang, sp. nov., N. virgula Liu W., Ahrens & Yang, sp. nov., and N. zhehaoi Liu W., Ahrens & Yang, sp. nov. The habitus and male genitalia of the new species are illustrated, and a map shows the distribution of the new species. Furthermore, new records of three known species are given.